Impact of Modified Piston - A Review - Manavalan, S.; Rai, Ramesh; Ranjan Kumar, Ravi; Kumar Chaudhary, Ritesh; Kumar Chaudhary, Subodh (International Journal of Psychosocial Rehabilitation, 2019)
The piston could be the heart of the engine, and its operating condition is the most unhealthy one amongst the key elements of the engine within the work. A piston could be a section of responding pistons responding pumps, gas compressors, and gas chambers among alternative comparative systems. It’s the moving half that’s contained by a barrel and is formed airtight by piston rings. During a piston, its motivation is to exchange force from growing gas within the barrel to the rotating shaft through a piston bar and, in addition, associating pole rod. The most objective is to analyze and analyze the behavior stress and structural analysis of the changed piston at the 64000 engine condition throughout the combustion method. This work advances by utilizing finite component analysis to anticipate the upper stress and significant space on the part.